An Econometric Analysis of the Impact of Real Effective Exchange Rate on Economic Activities in Nepal - Thapa, Nara Bahadur (NRB Economic Review, 2002)
This paper tests the relationship between REER and GDP on the Nepalese economy. In the literature, two channels of transmission exist for the real exchange rate to affect economic activities; these are the aggregate demand channel and the aggregate supply channel. The traditional view has it that the real exchange rate operates through the aggregate demand channel. This means that the depreciation of the real exchange rate enhances the international competitiveness of domestic goods, boosts net exports and eventually enlarges GDP. The aggregate supply channel, on the other hand, purports that the depreciation of the real exchange rate increases the cost of production and helps redistribute income in favour of the rich. These two effects lower aggregate demand causing economic contraction. The empirical study shows that the traditional view holds for Nepal and implies that Nepal should at least keep the real exchange rate constant.